Effect of Supplementing Ground Leaf of Misai (Orthosiphon stamineus) in Diet on Growth Performance of Broiler Chickens - Masnindah Malahubban; A A Zakry (Jurnal Ilmu Ternak dan Veteriner, 2022)
The use of herbs in animal nutrition is one of the important approaches in overcoming the disadvantages of excessive use of artificial chemicals in animal nutrition. The present study was done to evaluate response of broilers feeding on a diet supplemented with the ground leaf of misai (Orthosiphon stamineus). The birds in this, study were 160 one-day-old male broiler chickens, given ad libitum water and feed for up to 20 days. Treatments were given to 21-day-old male broiler chickens. Data was collected and evaluated after slaughtering 42-day- male broiler chickens. It was shown that supplementing broiler diets with O. stamineus powdered leaf at a rate of 8 g/kg resulted in growth performance comparable to tetracycline and Vitamin E supplementation. It was also shown that supplementing the diet with 8 g/kg O. stamineus had a blood enzyme-lowering effect. In broilers receiving tetracycline supplementation, however, significant serum enzyme activity was observed. Results also showed that 8 g/kg of ground O. stamineus leaf in the diet was equivalent to 200 mg/kg Vitamin E supplementation. Therefore, O. stamineus leaf powder can promote organic, safe, and sustainable broiler chicken production, and as diet supplement.